Government Spending and Tax Revenue Decentralization and Public Sector Efficiency: Do Natural Disasters Matter? - António Afonso; Jo\~ao Tovar Jalles; Ana Venâncio (Center for Economic Studies and ifo Institute (CESifo), 2023)
We assess notably how do extreme events affect the public sector efficiency of decentralized governance. Hence, we empirically link the public sector efficiency scores, to tax revenue and spending decentralization. First, we compute government spending efficiency scores via data envelopment analysis. Second, relying on panel data and impulse response approaches, we estimate the effect of decentralization on public sector efficiency and how extreme natural disasters mediate this relationship. The sample covers 36 OECD countries between 2006 and 2019. Our results show that tax revenue decentralization decreases public sector efficiency, while spending decentralization and a regional authority index are positively related to public sector efficiency, both for local projections and panel analysis. For instance, efficiency rises by 10 percent following a spending decentralization shock (reaching over 20 percent after 4 years). Nevertheless, in cases of natural disasters, spending decentralization reduces public sector efficiency. Specifically, in the presence of most extreme natural disasters, the improvement in public sector efficiency after a spending decentralization shock is smaller than in their absence. Moreover, extreme natural disasters also deteriorate the negative effect of tax revenue decentralization on public sector efficiency. These results suggest that sub-national discretionary spending and tax revenue responses might be less fruitful when such extreme events occur.
Keywords: C14; C23; E62; H11; H50; 330; public sector efficiency; data envelopment analysis; local projections; revenue decentralization; spending decentralization; natural disasters; OECD